Dermatomyositis: A dermatological perspective - Deepthi Ravi; Smitha Prabhu (Wolters Kluwer Medknow Publications, 2019)
Dermatomyositis (DM) is an autoimmune idiopathic inflammatory myopathy which has distinctive skin lesions, specific autoantibodies, and most importantly, symmetrical proximal muscle weakness and muscle inflammation of subacute onset. Some cases of DM present with only characteristic skin lesions without muscle disease and referred to as clinically amyopathic DM. Characteristic skin lesions include violaceous discoloration around the eyelids (heliotrope rash), erythematous rash over the face, erythematous scaly papules over the interphalangeal and metacarpophalangeal joints (Gottron's papules), erythema over the same joints (Gottron's sign), photosensitive pruritic erythema over the anterior chest and neck (V-sign), erythema extending to the shoulders and back (Shawl sign), distorted cuticles with dilated capillary loops over the proximal nail folds, and hyperkeratotic fissured skin over the palms and lateral aspect of the fingers (Mechanic's hands). Causes for mortality and morbidity in DM include malignancy, respiratory disease, and cardiac disease. After ruling out internal associations, Mangement involves photoprotection and medications including systemic corticosteroids, antimalarials, mycofenolate mofetil, biologicals and IV immunoglobulins, depending upon patient parameters.